Further Descriptive and Predictive Evidence on Alternative Time-Series Models for Quarterly Earnings - Lorek, Kenneth S.; Icerman, Joe D.; Abdulkader, Abdullah A. (Journal of Accounting Research, 1983)
Quarterly earnings, Predictive ability, Time-series, Goodness-of-fit